ECONOMIC VIABILITY OF RICE (Oryza sativa L.) AND CASSAVA (Manihot esculenta Crantz), IN A PRODUCTION SYSTEM OF PIJUAYO (Bactris gasipaes Kunth) IN LORETO, PERU - CUMARI LAULATE, Elías (2020)
The objective of the study was to determine the economic viability of a productive system of pijuayo (Bactris gasipaes Kunth) for fruit, associated with rice (Oryza sativa L.) and cassava (Manihot esculenta Crantz). The research was carried out in three experimental plots located along Iquitos-Nauta highway, Loreto, Peru: 1) Experimental Field El Dorado km 25.5, 2) El Paujil Experimental Plot km 35.5, and 3) Experimental Plot Bolloquito km 75.5. A relational analysis was employed to assess the economic viability. Rice and cassava components of the Pijuayo fruit production system were distributed in three random blocks (04 genotypes, plus one control, local genotype). We found that rice and cassava were economically profitable. The plot of El Dorado having the highest profitability. Thus, in the Pijuayo fruit productive system, rice and cassava may provide sufficient economic income in the first years. Therefore, the productive agrarian system of pijuayo associated with rice and cassava is economically and financially viable.